Washing with hope: evidence of improved handwashing among children in South Africa from a pilot study of a novel soap technology - Justine Burns; Brendan Maughan-Brown; Âurea Mouzinho (BMC, 2018)
Abstract Background While regular handwashing effectively reduces communicable disease incidence and related child mortality, instilling a habit of regular handwashing in young children continues to be a challenging task, especially in developing country contexts. This randomised controlled pilot study assessed the effect of a novel handwashing intervention - a bi-monthly delivery of a colourful, translucent bar of soap with a toy embedded in its centre (HOPE SOAP©) - on children's handwashing behaviour and health outcomes. Methods Between September and December 2014, 203 households in an impoverished community in Cape Town, South Africa, were randomised (1:1) to the control group or to receive HOPE SOAP©. Of all children (N = 287) aged 3-9 years and not enrolled in early childhood development programmes, 153 residing in intervention households received a bar of HOPE SOAP© every two weeks (total of 4 bars). Children in control households received a colourful, translucent bar of soap of equal size to HOPE SOAP©, with a toy alongside it. Two 'snack tests' (children were offered crackers and jam) were used to provide objective observational measures of handwashing. Through baseline and endline surveys, data were collected from caregivers on the frequency (scale of 1-10) of handwashing by children after using the toilet and before meals, and on soap-use during handwashing. Data on 14 illnesses/symptoms of illness experienced by children in the two weeks preceding the surveys were collected. Multivariable Ordinary Least Squares regression analyses were used to assess the intervention effect on handwashing behaviours and health outcomes. Results At endline, HOPE SOAP© children were directly observed as being more likely to wash their hands unprompted at both snack tests (49% vs 39%, β: 0.10, p = 0.27). They were more likely to score ≥8/10 for using soap when washing their hands (β: 0.14, p = 0.011). HOPE SOAP© children, in general, had better health outcomes, and those who used the soap as intended, and did not cheat to remove the toy from the soap, were less likely to have been ill (β: − 0.15, p = 0.049). Conclusions Results point towards HOPE SOAP© being an effective intervention to improve handwashing among children. Further research on this novel handwashing intervention is warranted. Trial registration NCT03280771 (www.clinicaltrials.gov) retrospectively registered on 8 September 2017.